Tennis Tournaments from the Perspective of Sport Tourism - BANCIU, Alexandru-Nicolae; POPIRLAN, Claudiu-Ionut; COSMA, Germina (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.14.2(66).13, 2023)
Tourism development over the last years led to an increase in the number of sport events attendees and, on the other hand, the sport events expansion generated the growth of sport related tourism. Sport tourism is a meaningful branch of overall tourism referring to the individuals participating in sport events both actively and passively. Referring to tennis tournaments, there has been a constant increase in media publicity, advertising space for the sponsors and the number of spectators. Thus, tennis, as a sport and a touristic product, has a significant contribution in attracting tourists and in regional development. Long-term development strategies should consider the socioeconomic traits of tennis related tourism.